Short Text Messages (SMS) as an Additional Tool for Notifying Medical Staff in Case of a Hospital Mass Casualty Incident. (12th October 2015) - Timler, Dariusz; Bogusiak, Katarzyna; Kasielska-Trojan, Anna; Neskoromna-Jędrzejczak, Aneta; Gałązkowski, Robert; Szarpak, Łukasz
Abstract: Objective: The aim of the study was to verify the effectiveness of short text messages (short message service, or SMS) as an additional notification tool in case of fire or a mass casualty incident in a hospital. Methods: A total of 2242 SMS text messages were sent to 59 hospital workers divided into 3 groups (n=21, n=19, n=19). Messages were sent from a Samsung GT-S8500 Wave cell phone and Orange Poland was chosen as the telecommunication provider. During a 3-month trial period, messages were sent between 3:35 PM and midnight with no regular pattern. Employees were asked to respond by telling how much time it would take them to reach the hospital in case of a mass casualty incident. Results: The mean reaction time (SMS reply) was 36.41 minutes. The mean declared time of arrival to the hospital was 100.5 minutes. After excluding 10% of extreme values for declared arrival time, the mean arrival time was estimated as 38.35 minutes. Conclusions: Short text messages (SMS) can be considered an additional tool for notifying medical staff in case of a mass casualty incident. ( Disaster Med Public Health Preparedness . 2016;10:38–41)